Hooked on Smartphones: Smartphone Usage Pattern and Related Health Risks among Medical Students in a Tertiary Centre at Kolkata - Ahmad, Shamshad; Goswami, Shweta; Mishra, Shruti; Chaudhary, Anurag; Karmakar, Rhitam; Verma, Dheeraj (National Journal of Community Medicine, 2018)
Introduction: Globally, usage of smartphones is been increased in the recent years. Besides being beneficial gadget, it has many dis- advantages like reduction in work efficiency, psychological addic- tion etc. The study aimed to find out the usage pattern and pro- portion of various risky behaviours and related health risks of Smartphone uses among medical students. Methods: It was a descriptive cross section study. The study was conducted during May 2016. Responses were taken online through google form. WhatsApp and email platform were used for this. Result: Smartphone usage duration was 835 hours’ average per day for total sample. Use of Smartphone while driving was signif- icantly higher among hosteller. Keep it near head, use while on charge, use while crossing road, headache, back pain, and painful fingers were significantly high in those who were using it for > 4 hours per day. 18% respondents were aware of 20-20-20 rule while using any electronic devices. Conclusion: Smartphone was most commonly used for social networking. Using before going to sleep, keeping it near head while sleeping, using while charging or near to discharge, were most prevalent health risky behaviour. Lack of sleep, headaches, back pain, neck pain and irritation in eye were common health risks. Awareness about using smartphone in right way was very poor.